Manufacturing design and static analysis of a gear shaft - O. Okonokhua, Israel; Bodzás, Sándor (Journal of Production Engineering, 2024)
This paper presents a gear shaft design that was constructed with the use of Solidworks, the manufacturing process of the design done by the use of the Edgecam software and also a Finite Element Analysis (FEA) which includes examining the part's displacement behavior with corresponding stress and deformation. The 3-dimensional finite element simulation and meshing of the model was done with the ANSYS Workbench. Boundary requirements including external loads were also utilized. The manufacturing design was done in two parts due to the high level of complexity associated with the gear shaft. The first part included the parametric configurations used for machining one end of the gear shaft and the second part included the parametric configurations used for machining the other end of the gear shaft. This means that when the machining process has to be done on the CNC machine, there will be two separate CNC codes to be utilized which can run successively. During the manufacturing design phase, important information was obtained, such as the overall time for machining of one or both ends of the gear shaft as well as the safety conditions that were utilized during the process.